Using of suiferrovit-A as a pathogenic agent in bovine anaplasmosis - V. G. Minasyan; J. G. Tkachenko (Российский паразитологический журнал, 2016)
Therapeutic efficiency of antibiotic therapy at bovine anaplasmosis increases with simultaneous use of drugs stimulating the hematopoietic system. Suiferrovit-A contributes to the restoration of physiological functions of cattle at anaplasmosis.